Contralateral Sensory and Pain Perception Changes in Patients With Unilateral Neuropathy. (27th July 2021) - Enax-Krumova, Elena; Attal, Nadine; Bouhassira, Didier; Freynhagen, Rainer; Gierthmühlen, Janne; Hansson, Per; Kuehler, Bianca M.; Maier, Christoph; Sachau, Juliane; Segerdahl, Märta; Tölle, Thomas; Treede, Rolf-Detlef; et al.
Abstract : Objective: To test whether contralateral sensory abnormalities in the clinically unaffected area of patients with unilateral neuropathic pain are due to the neuropathy or pain mechanisms. Methods: We analyzed the contralateral clinically unaffected side of patients with unilateral painful or painless neuropathy (peripheral nerve injury [PNI], postherpetic neuropathy [PHN], radiculopathy) by standardized quantitative sensory testing following a validated protocol. Primary outcome was the independent contribution of the following variables on the contralateral sensory function using generalized linear regression models: pain intensity, disease duration, etiology, body area, and sensory patterns in the most painful area. Results: Among 424 patients (PNI n = 256, PHN n = 78, radiculopathy n = 90), contralateral sensory abnormalities were frequent in both painful (n = 383) and painless (n = 41) unilateral neuropathy, demonstrating sensory loss for thermal and mechanical nonpainful stimuli and both sensory loss and gain for painful test stimuli. Analysis by etiology revealed contralateral pinprick hyperalgesia in PHN and PNI. Analysis by ipsilateral sensory phenotype demonstrated mirror-image pinprick hyperalgesia in both mechanical and thermal hyperalgesia phenotypes. Pain intensity, etiology, and affected body region predicted changes in only single contralateral somatosensory parameters. Disease duration had no impact on the contralateral sensory function. Conclusion: Mechanisms of sensory loss seem to spread to the contralateral side in both painful and painless neuropathies. Contralateral spread of pinprick hyperalgesia was restricted to the 2 ipsilateral phenotypes that suggest sensitization; this suggest a contribution of descending net facilitation from supraspinal areas, which was reported in rodent models of neuropathic pain but not yet in human patients.